Structure of Sea Urchin (Echinoidea) Community in The Tidal Zone of Kuta Mandalika Bay - Hidayat, Ismadi Dwi Saputra; Candri, Dining Aidil; Ahyadi, Hilman (Jurnal Biologi Tropis, 2025)
This study aims to examine the structure of sea urchin (Echinoidea) communities in the tidal zone of Kuta Mandalika Bay. The research was conducted in August 2024 at three different stations: River Estuary (Station 1), KEK Tourism Area (Station 2), and Mangrove Ecosystem (Station 3). Data collection was carried out using purposive sampling with line transects and plots to identify species, abundance, and environmental parameters (substrate and salinity). The results identified four sea urchin species: Diadema setosum, Tripneustes gratilla, and Enchinometra mathei. Station 2 exhibited the highest diversity and abundance (H' = 2,31; 68.70% abundance), characterized by a rocky sand substrate and salinity of 30 ppt. In contrast, no sea urchins were found at Station 1, which had a muddy sand substrate and lower salinity (28 ppt). Station 3 showed moderate diversity (H' = 1.77) with 50% abundance. Environmental factors such as substrate type, salinity, and the presence of mangrove vegetation significantly influenced the distribution of sea urchins. This study highlights the critical role of habitat characteristics in shaping sea urchin community structure in the tidal zone.